Optimal Sizing and Comparative Analysis of Renewable Energy Integration for the Existing Microgrid System in Kadan Island - Htun, Khin Thandar; Swe, Wunna (AI Society & STMIK Indonesia, 2024)
The rapid depletion of fossil fuels and the necessity for reduced carbon emissions have led to an increased focus on renewable energy resources. The existing microgrid system comprises solely a diesel generator and a small portion of hydropower. Currently, Kadan Island relies mainly on diesel generators to supply power, resulting in a significantly higher cost of energy in comparison to other areas. Furthermore, there is still not enough electricity available on the entire island of Kadan. However, research has shown that integrating renewable-based systems with storage technologies into existing systems can help mitigate these issues. Therefore, the main objective of this paper is to investigate the optimal size and operation of a hybrid renewable system on the Myanmar Islands. The optimization process will focus on minimizing the net present cost (NPC) and cost of energy (COE) of the selected location. Additionally, the island's network will be analyzed under normal operating conditions with different scenarios, and the best scenario for the existing microgrid on Kadan Island will be recommended.